Why Industry Propaganda and Political Interference Cannot Disguise the Inevitable Role Played by Human Exposure to Aluminum in Neurodegenerative Diseases, Including Alzheimer’s Disease - Exley, Christopher (Frontiers in Neurology, 2014)
In the aluminium age it is clearly unpalatable for aluminium, the globe’s most successful metal, to be implicated in human disease. It is unpalatable because for approximately 100 years humans have reaped the rewards of the most abundant metal of the Earth’s crust without seriously considering the potential consequences for human health. The aluminium industry is a pillar of the developed and developing world and irrespective of the tyranny of human exposure to aluminium it cannot be challenged without significant consequences for businesses, economies and governments. However, no matter how deep the dependency nor unthinkable the withdrawal, science continues to document, if not too slowly, a burgeoning body burden of aluminium in humans. Herein I will make the case that it is inevitable both today and in the future that an individual’s exposure to aluminium is impacting upon their health and is already contributing to, if not causing, chronic diseases such as Alzheimer’s disease. This is the logical, if uncomfortable, consequence of living in the aluminium age.